1999
DOI: 10.1046/j.1365-2567.1999.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo selective expansion of a tumour‐specific cytotoxic T‐cell clone derived from peripheral blood of a melanoma patient after vaccination with gene‐modified autologous tumour cells

Abstract: SUMMARYMelanoma-speci®c cytotoxic T lymphocytes (CTL) can be generated from peripheral blood lymphocytes (PBL) by mixed lymphocyte±tumour cell cultures. Analysis of CTL precursor frequencies in peripheral blood of melanoma patients is generally used for immunomonitoring purposes to evaluate vaccination ef®cacy. At present, it is unclear whether PBL-derived CTL generated in vitro are indicative of an anti-tumour immune response in vivo. Three tumour-speci®c human leucocyte antigen (HLA)-B/C-restricted CTL clone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…These results were consistent with previous findings that T cells infiltrating in tumor lesions comprise high numbers of clonal expansion 29 and that the proliferation of oligoclonal T cells in tumor lesions would be massively induced in response to tumor-associated antigenic peptides. 30 Our study showed the diversity of TCRs, which was calculated by Shannon diversity index 31 had no difference compared with adjacent non-tumor tissues in NSCLC ( Figure 1 ). However, a recent study that presented data from 15 lung cancer patients showed that significantly higher TCR diversity was observed in tumor tissues than in normal lung tissues, 32 the increases or decreases of the diversity of TCRs in tumors relative to paired normal tissues are inconsistent in different cancer types 33 , 34 , 35 or even same type in different studies.…”
Section: Discussionmentioning
confidence: 66%
“…These results were consistent with previous findings that T cells infiltrating in tumor lesions comprise high numbers of clonal expansion 29 and that the proliferation of oligoclonal T cells in tumor lesions would be massively induced in response to tumor-associated antigenic peptides. 30 Our study showed the diversity of TCRs, which was calculated by Shannon diversity index 31 had no difference compared with adjacent non-tumor tissues in NSCLC ( Figure 1 ). However, a recent study that presented data from 15 lung cancer patients showed that significantly higher TCR diversity was observed in tumor tissues than in normal lung tissues, 32 the increases or decreases of the diversity of TCRs in tumors relative to paired normal tissues are inconsistent in different cancer types 33 , 34 , 35 or even same type in different studies.…”
Section: Discussionmentioning
confidence: 66%
“…In a previous report, it was shown that vaccination with autologous melanoma cells transfected ex vivo to produce IL -7 induced, in PBL of the treated patients, both MHC-restricted as well as MHC -unrestricted lytic activity against the autologous melanoma. 13,33,34 In addition, a number of clones with antitumor specificity could be derived from PBL of one of the patients. 33 In spite of documentation of this antitumor Tcell response, no durable clinical responses were, however, observed.…”
Section: Discussionmentioning
confidence: 99%
“…13,33,34 In addition, a number of clones with antitumor specificity could be derived from PBL of one of the patients. 33 In spite of documentation of this antitumor Tcell response, no durable clinical responses were, however, observed. 13 Ex vivo sensitisation of pre -and postvaccine PBLs that identify a vaccine-specific systemic T cell response to immunisation is, however, not an unusual finding even in the absence of clinical responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxicity assays Cytolytic activity of CTL against melanoma cells, EBV‐B cells and K562 was determined in a 6 h LDH‐release assay as described elsewhere [15]. Briefly, 5 × 10 3 target cells were cultured in triplicates with varying numbers of effector cells for 6 h at 37°C in 5% CO2.…”
mentioning
confidence: 99%